Effects of Synthesis Conditions on the Nanostructure of Hybrid Sols Produced by the Hydrolytic Condensation of (3-Methacryloxypropyl)trimethoxysilane - Santilli, Celso Valentim [UNESP]; Sarmento, V. H. V. [UNESP]; Dahmouche, K.; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Amer Chemical Soc, 2009)
Polysilsesquioxanes containing methacrylate pendant groups were prepared by the sol-gel process through hydrolysis and condensation of (3-methacryloxypropyl)trimethoxysilane (MPTS) dissolved in a methanol/methyl methacrylate (MMA) mixture. The effects of different water, MMA, and methanol contents, as well as of pH, on the nanoscopic and local structures of the system, at advanced stages of the condensation reaction, were studied by small-angle X-ray scattering (SAXS) and (29)Si nuclear magnetic resonance (NMR) spectroscopy, respectively. SAXS results indicate that the nanoscopic features of the hybrid sol could be described by a hierarchical model composed of two levels, namely (i) silsesquioxane (SSQO) nanoparticles Surrounded by the methacrylate pendant groups and the methanol/MMA mixture. and (ii) aggregation zones or islands containing correlated SSQO nanoparticles, embedded in the liquid medium. The (29)Si NMR results Show that the inner Structures of SSQO nanoparticles produced at pH 1 and 3 were built Up of polyhedral structures. mainly cagelike octamers and small linear oligomers, respectively. Irrespective of MMA and methanol contents, for a [H(2)O]/[MPTS] ratio higher than or equal to 1, the SSQO nailoparticles produced at pH I exhibit an average condensation degree (CD approximate to 69-87%) and average radius of gyration (R(g) approximate to 2.5 angstrom) larger than those produced at pH 3 (CD approximate to 48-67% and R(g) approximate to 1.5 angstrom). Methanol appears to act as a redispersion agent, by decreasing the number of particles inside the aggregation zones, while the addition of MMA induces a swelling of the aggregation zones.